Growth on sublexical fluency progress monitoring measures in early kindergarten and relations to word reading acquisition. (April 2020) - Clemens, Nathan H.; Lee, Kejin; Henri, Maria; Simmons, Leslie E.; Kwok, Oi-man; Al Otaiba, Stephanie
Abstract: Fluency with skills that operate below the word level (i.e., sublexical), such as phonemic awareness and alphabetic knowledge, may ease the acquisition of decoding skills (Ritchey & Speece, 2006). Measures of sublexical fluency such as phoneme segmentation fluency (PSF), letter naming fluency (LNF), and letter sound fluency (LSF) are widely available for monitoring kindergarten reading progress, but less is known about the relative importance of growth in each skill across the early months of formal reading instruction and their relation to subsequent decoding acquisition. With a sample of kindergarten students at risk for reading difficulties, this study investigated the extent to which initial status and growth in PSF, LNF, and LSF, administered on a progress-monitoring basis during the fall of kindergarten, were differentially predictive of word reading fluency skills at mid-year and growth across the second half the school year. We used two different fluency-based progress monitoring measures of word reading across the spring, one consisting entirely of phonetically regular consonant-vowel-consonant words, and the other that included phonetically regular and irregular words that varied in length. Results indicated that although initial status and fall growth in all sublexical fluency measures were positively associated with subsequent word reading, LSF across the fall of kindergarten was the strongest overall predictor of mid-year level and growth on both word reading measures, and unique in its prediction over the effects of LNF and PSF. Results underscore the importance of letter-sound knowledge for word reading development, and provide additional evidence for LSF as a key index of progress for at-risk learners across the early months of formal reading instruction.